Regulatory T Cells Expressing Tumor Necrosis Factor Receptor Type 2 Play a Major Role in CD4+ T-Cell Impairment During Sepsis. (22nd July 2020) - Gaborit, Benjamin J; Roquilly, Antoine; Louvet, Cédric; Sadek, Abderrahmane; Tessoulin, Benoit; Broquet, Alexis; Jacqueline, Cédric; Vourc'h, Mickael; Chaumette, Tanguy; Chauveau, Marie; Asquier, Antoine; Bourdiol, Alexandre; et al.
Abstract: Sepsis causes inflammation-induced immunosuppression with lymphopenia and alterations of CD4 + T-cell functions that renders the host prone to secondary infections. Whether and how regulatory T cells (Treg) are involved in this postseptic immunosuppression is unknown. We observed in vivo that early activation of Treg during Staphylococcus aureus sepsis induces CD4 + T-cell impairment and increases susceptibility to secondary pneumonia. The tumor necrosis factor receptor 2 positive (TNFR2 pos ) Treg subset endorsed the majority of effector immunosuppressive functions, and TNRF2 was particularly associated with activation of genes involved in cell cycle and replication in Treg, probably explaining their maintenance. Blocking or deleting TNFR2 during sepsis decreased the susceptibility to secondary infection. In humans, our data paralleled those in mice; the expression of CTLA-4 was dramatically increased in TNFR2 pos Treg after culture in vitro with S. aureus . Our findings describe in vivo mechanisms underlying sepsis-induced immunosuppression and identify TNFR2 pos Treg as targets for therapeutic intervention. Abstract : Treg are involved early in immunosuppression during sepsis. The TNFR2 pos Treg subset appears to induce a state of immunosuppression and increases the susceptibility to secondary infection. Inhibiting TNFR2 pos Treg could represent a prophylactic treatment of pneumonia in the intensive care unit.